Peningkatan Kualitas Kesehatan Masyarakat Melalui Program PHBS, Pencegahan Penyakit dan Pemberian Nutrisi Pada Anak Usia Dini di Desa Muara Hungi Kabupaten Hulu Sungai Tengah - Rahima, Annisa; An'amta, Dimas Asto Aji; Setiawan, Muhammad Dedy; Fajriah, Syarifah; Sudrajat, Putri Yessa; Mariyati, Heni; Rahmadi; Mahat, Dio Kristian; Sabrina, Siti Salma Nur; Putri, Tracy Ananda; Lestari, Citra Amalia (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
Muara Hungi Village, located in the Meratus Mountains, South Kalimantan, faces significant challenges related to health and environmental sanitation. The villagers, who mainly work as farmers and fishermen, maintain a traditional socio-cultural lifestyle. The primary issues include a lack of awareness regarding environmental cleanliness, proper sanitation, and balanced nutrition, particularly for children. This Community Service Program aims to improve the community's health quality through the implementation of Clean and Healthy Living Behaviors (PHBS), nutrition education, disease prevention for children, health counseling, and training of health cadres. The local community was actively involved in the planning and implementation process, allowing for an effective transfer of knowledge and skills. Additionally, the program focused on strengthening local institutions, such as community health centers (puskesmas) and schools, to run sustainable health programs. Using a live-in, participatory, cultural, and community empowerment approach, this program successfully fostered greater health awareness among villagers, particularly in schools and community health posts (posyandu). The program outcomes indicated improvements in school cleanliness practices, reduced disease risks, and increased understanding of balanced nutrition to prevent stunting in children. This program had a significant impact on improving the quality of life for the residents of Muara Hungi Village. The program’s success was evident not only in the physical health outcomes but also in the increased community participation in social activities centered on public health. This further highlights the potential for long-term sustainability, with the community acting as the primary driver of change in Muara Hungi Village.